Contribution of Topical Agents such as Hyaluronic Acid and Silver Sulfadiazine to Wound Healing and Management of Bacterial Biofilm - Francesco De Francesco; Michele Riccio; Shiro Jimi (Medicina, 2022)
Background and Objectives: Wound healing is commonly associated with critical bacterial colonization or bacterial infection, which induces prolonged inflammation, resulting in delayed re-epithelialization. An appropriate wound dressing requires a humid environment, which also functions as a barrier against bacterial contamination and will accelerate a regenerative response of the wound. Silver sulfadiazine (SSD) is used to prevent wound infection. Hyaluronic acid (HA) is an extracellular matrix component involved in tissue regeneration. This retrospective study was conducted to evaluate the effectiveness of cream and gauze pads based on hyaluronic acid at low molecular weight (200 kDa) and silver sulfadiazine 1% in the wound healing process. In addition, we examined SSD action on biofilms in vitro and on animal wounds, obtaining positive outcomes therefrom. Materials and Methods: We selected 80 patients with complicated chronic wounds of different etiologies, including diabetes mellitus (10), post-traumatic ulcers (45), burns (15), and superficial abrasion (10). Results: After 8 weeks, ulcer size was decreased in 95 ± 2% of the treated patients; a significant reduction in the inflammatory process was observed from day 14 onwards (p < 0.01 vs. baseline), considering improvement of the surrounding skin and reduction of the bacterial load. The SSD treatment decreased bacterial colony proliferation, both in planktonic state and in biofilm, in a dose-dependent manner on the wound but inhibited the development of tissue granulation at the highest dose (800 μg/wound). Conclusions: In conclusion, the combined action of SSD and HA is clinically effective in improving wound healing.